Bordering Ecosystems: The Rhetorical Function of Characterization in Gray Wolf Management. Issue 4 (4th July 2017) - Phillips, Aaron T.
Abstract : Decisions about iconic species such as the wolf provide a key index of human–nature relations. The gray wolf's reintroduction in the USA has been controversial, particularly at the interface of state versus federal management. This essay analyzes discourse surrounding this controversy, focusing on how wolves are characterized as ecological and social actors in official correspondence and management plans. I interpret this textual evidence by drawing from social theory regarding sovereignty, discipline, and population, including studies on bordering practices imposed on humans. As with humans, bordering practices in the case of the wolf may illuminate how political forces impose physical and discursive limits upon mobile bodies motivated to move across political borders by powerful exigencies of need. The essay seeks to amplify understanding about how regimes of power enact difference from "others" whose presence strongly influences the health of ecosystems and economies.